Therapeutic evaluation and analysis of complications of ethanol sclerotherapy for intramuscular vascular malformations: a single-center retrospective study - Jin, Cai-Jun; Wang, Qian; Wang, Min; Chen, Yong; Yuan, Si-Ming (Frontiers in Surgery, 2023)
Background Intramuscular venous malformations (IMVMs) can cause pain and contracture deformity, leading to dysfunction of limbs. Ethanol sclerotherapy is one of the main treatments for IMVMs. This study aims to evaluate the efficacy and the complications associated with intravascular ethanol sclerotherapy for IMVMs and to provide a comprehensive summary of clinical experiences for future reference. Methods A retrospective analysis was conducted on a cohort of 118 patients diagnosed with IMVMs who were treated with ethanol sclerotherapy in our center between 2006 and 2021. The plastic surgeons utilized a standardized collection pro forma to record the clinical data. Furthermore, a follow-up period ranging from 6 months to 5 years was implemented to assess the relief of symptoms, the change of lesion size, and the recovery of functional outcomes. In addition, an analysis of long-term complications was conducted. Results The clinical symptoms of the patients in this group included pain, swelling, and limited movement. On average, 5.61 mL (range 2–14 mL) of ethanol was used during the sclerotherapy procedure. The intraoperative and early postoperative complications were successfully relieved by means of timely intervention, as observed during the follow-up period. Based on the MRI results, the sizes of the lesions in 19% of the cases were significantly decreased, while a slight decrease was observed in 39% of the cases. During the follow-up period, it was found that only eight out of the 118 patients included in this study experienced long-term complications related to sclerotherapy. Conclusions Although ethanol sclerotherapy has proven to be an effective first-line treatment for IMVMs, it is associated with a variety of adverse reactions and short- and long-term complications. Surgeons are required to perform operations prudently and provide timely medical intervention for postoperative complications.